Equity, Commodity, and Distillate Risk for Oil Upstream Producers and Downstream Consumers - Scott Alan Carson (Center for Economic Studies and ifo Institute (CESifo), 2023)
The oil and gas industry's role in economic activity is hard to overstate. This study considers upstream, midstream, and downstream oil producer returns and risk compared to downstream oil consumers in airlines, ground-freight, railroads, and tire manufacturing. Between 2000 and 2020, the oil and gas industry had the lowest expected returns, greater risk, and only Integrated producer returns approached downstream oil and gas consumer risk-return profiles. Railroad companies were the least risky with the highest returns, followed by tire manufacturers, airlines, and freight companies. Equity, commodity, and distillate markets positively price risk into oil and gas producer returns, and upstream producers had greater project and equity market risk than downstream consumers. Most downstream oil consumer equity returns are positively related to equity and commodity market risk, while a few downstream commercial consumers have negative equity and commodity return variation, indicating that crude oil is an input to downstream consumers.
Keywords: L62; L72; L93; L91; L92; 330; oil and gas; air transportation; ground freight; railroads; tire manufacturing